Tunnelling into InAs quantum dots - Hill, Richard John Allan (2003)
This thesis describes an experimental study of the electronic properties of semiconductor heterostructure tunnel devices. InAs self-assembled quantum dots (QDs) are incorporated into the barrier layer of a GaAs/AlAs/GaAs tunnel diode. When a voltage, V, is applied across the device, we observe resonant features in the tunnel current, I, whenever an electron state in one of the qds comes into resonance with an occupied electron state in the emitter. We employ an electron state of a single qd as a spectroscopic probe of a two-dimensional electron system (2DES), from the Fermi energy to the subband edge [1]. For magnetic field B applied parallel to the current, we observe peaks in the I(V) characteristics corresponding to the formation of Landau levels in the 2DES. We obtain quantitative information about the energy dependence of the quasiparticle lifetime, Tqp, of the 2DES. We find that Tqp ~ 2.5 hbar=(Ef - E), in contrast with the expectation for a normal Fermi liquid, but in agreement with predictions for a Fermi liquid state of a disordered 2DES. Close to filling factor nu = 1 we observe directly the exchange enhancement of the g factor.